A review of vagus nerve stimulation as a therapeutic intervention - Johnson RL; Wilson CG (Dove Medical Press, 2018)
Rhaya L Johnson,1 Christopher G Wilson1,2 1Lawrence D Longo MD Center for Perinatal Biology, Department of Basic Sciences, Loma Linda University, Loma Linda, CA, USA; 2Department of Pediatrics, Loma Linda University, Loma Linda, CA, USA Abstract: In this review, we provide an overview of the US Food and Drug Administration (FDA)-approved clinical uses of vagus nerve stimulation (VNS) as well as information about the ongoing studies and preclinical research to expand the use of VNS to additional applications. VNS is currently FDA approved for therapeutic use in patients aged >12 years with drug-resistant epilepsy and depression. Recent studies of VNS in in vivo systems have shown that it has anti-inflammatory properties which has led to more preclinical research aimed at expanding VNS treatment across a wider range of inflammatory disorders. Although the signaling pathway and mechanism by which VNS affects inflammation remain unknown, VNS has shown promising results in treating chronic inflammatory disorders such as sepsis, lung injury, rheumatoid arthritis (RA), and diabetes. It is also being used to control pain in fibromyalgia and migraines. This new preclinical research shows that VNS bears the promise of being applied to a wider range of therapeutic applications. Keywords: vagus nerve stimulation, pediatrics, inflammation, peripheral nerve stimulation, autonomic circuits